2022
DOI: 10.3390/ph15050551
|View full text |Cite
|
Sign up to set email alerts
|

Brain Glucose Hypometabolism and Iron Accumulation in Different Brain Regions in Alzheimer’s and Parkinson’s Diseases

Abstract: The aim of this study was to examine the relationship between the presence of glucose hypometabolism (GHM) and brain iron accumulation (BIA), two potential pathological mechanisms in neurodegenerative disease, in different regions of the brain in people with late-onset Alzheimer’s disease (AD) or Parkinson’s disease (PD). Studies that conducted fluorodeoxyglucose positron emission tomography (FDG-PET) to map GHM or quantitative susceptibility mapping—magnetic resonance imaging (QSM–MRI) to map BIA in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Additionally, a longitudinal study of cognitively normal adults showed that accumulation of iron in the putamen could predict its shrinkage (Daugherty and Raz, 2016). Although less investigated for associations between QSM and the other biomarkers of neurodegeneration, a combined 18 F-FDG-PET and QSM study in different AD cohorts revealed glucose hypometabolism and brain iron accumulation in the hippocampus, temporal, and parietal lobes (Rao et al, 2022).…”
Section: Association Of Quantitative Susceptibility Mapping With Neur...mentioning
confidence: 99%
“…Additionally, a longitudinal study of cognitively normal adults showed that accumulation of iron in the putamen could predict its shrinkage (Daugherty and Raz, 2016). Although less investigated for associations between QSM and the other biomarkers of neurodegeneration, a combined 18 F-FDG-PET and QSM study in different AD cohorts revealed glucose hypometabolism and brain iron accumulation in the hippocampus, temporal, and parietal lobes (Rao et al, 2022).…”
Section: Association Of Quantitative Susceptibility Mapping With Neur...mentioning
confidence: 99%
“…Another study found that excessive iron accumulation was associated with region-specific advanced atrophy ( Lee et al, 2013 , 2015 ). Brain iron abnormally accumulates in a number of neurological disorders such as AD, PD leads to the neurotoxicity of oxidative stress which can promote neuron loss and degeneration, and may manifest as brain atrophy ( Dixon et al, 2012 ; Ward et al, 2014 ; Rao et al, 2022 ; Yang et al, 2022 ). Lots of people believe that insulin resistance and diminished insulin signaling in the brain play a role in glucose hypometabolism ( Freiherr et al, 2013 ; Ferreira et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before AD pathogenesis, changes in glucose metabolism happen when oxidative damage builds up. Early-stage AD patients have significantly reduced glucose absorption, which suggests that the condition is preceded by altered glucose metabolism and elevated steady-state glucose concentrations [57]. In addition to facilitating glucose metabolism and influencing tau protein and Aβ processing, insulin in the brain is essential for learning, memory, neurite growth, and development.…”
Section: Hypo Metabolism Of Glucose In Admentioning
confidence: 99%
“…Additionally, increased GSK3/ activity encourages Tau phosphorylation and Aβ accumulation [56]. When set side by side to age-matched controls, AD patients show drastical and insignificant brain levels of insulin, insulin-like growth factor I (IGF-I), insulin-like growth factor II, and IGF-I receptor [57].…”
Section: Hypo Metabolism Of Glucose In Admentioning
confidence: 99%
See 1 more Smart Citation